Neuroprotective effects of mildronate in a rat model of traumatic brain injury - YEGEN, BERRAK; AKAKIN, DİLEK; YÜKSEL, MERAL; KOYUNCUOĞLU, TÜRKAN (ELSEVIER SCI LTD, 2019)
Objective: Traumatic brain injury (TBI) is one of the most common preventable causes of mortality and morbidity. Inflammation, apoptosis, oxidative stress, and ischemia are some of the important pathophysiological mechanisms underlying neuronal loss after TBI. Mildronate is demonstrated to be beneficial in various experimental models of ischemic diseases via anti-inflammatory, antioxidant, and neuroprotective mechanisms. This study aimed to investigate possible antioxidant, anti-inflammatory, antiapoptotic, and neuroprotective effects of mildronate in a rat model of TBI. Methods: A total of 46 male rats were divided into three groups of control, saline-treated TBI, and mildronate-treated TBI. Both TBI groups were subjected to closed-head contusive weight-drop injuries followed by treatment with saline or mildronate (100 mg/kg) administered intraperitoneally. The forebrain was removed 24h after trauma induction, the activities of myeloperoxidase (MPO) and caspase-3, levels of superoxide dismutase (SOD), luminol- and lucigenin-enhanced chemiluminescence were measured, and histomorphological evaluation of cerebral tissues was performed. Results: Increased MPO and caspase-3 activities in the vehicle-treated TBI group (p < 0.001) were suppressed in the mildronate-treated TBI group (p < 0.001). Similarly, increase in luminol and lucigenin levels (p < 0.001 and p < 0.01, respectively) in the vehicle-treated TBI group were decreased in the mildronatetreated TBI group (p < 0.001). Concomitantly, in the vehicle-treated TBI group, TBI-induced decrease in SOD activity (p < 0.01) was reversed with mildronate treatment (p < 0.05). On histopathological examination, TBI-induced damage in the cerebral cortex was lesser in the mildronate-treated TBI group than that in other groups. Conclusion: This study revealed for the first time that mildronate, exhibits neuroprotective effects against TBI because of its anti-inflammatory, antiapoptotic, and antioxidant activities. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Antiapoptotic effect; Diffuse brain injury; Mildronate; Neuroprotection; CEREBRAL-BLOOD-FLOW; ISCHEMIA-REPERFUSION INJURY; ACID OXIDATION INHIBITORS; SPINAL-CORD ISCHEMIA; GAMMA-BUTYROBETAINE; ISCHEMIA/REPERFUSION INJURY; CARNITINE BIOSYNTHESIS; SUPEROXIDE-DISMUTASE; PROTEIN EXPRESSION; DARBEPOETIN-ALPHA